A study on the hydrodechlorination reaction of dichlorodifluoromethane over Pd/AlF3 catalyst - Ahn, BS; Lee, SC; Moon, DJ; Lee, BG (ELSEVIER SCIENCE BV, 1996)
The hydrodechlorination reaction of dichlorodifluoromethane (CF2Cl2) has been studied under an atmospheric pressure at 130-210 degrees C over Pd/AIF(3) catalyst. The effects of various reaction conditions on the catalyst performance in terms of the reaction rate and product distributions were extensively investigated and the adsorption behaviours of H-2, CF2Cl2, CHF2Cl, CH2F2 and CH3F on the catalyst surface are compared. In addition, the plausible reaction scheme has been proposed based on the experimental observations. Under the assumption that the formation of two main products, CH2F2 and CH4, proceeds through the hydrogenation of intermediate species, CF2**, the reaction rate constants have been calculated by fitting the experimental data with the reaction rate expression.
Keywords: CHLOROFLUOROCARBONS; DECOMPOSITION; DESTRUCTION